2018
DOI: 10.1080/03650340.2018.1492714
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-induced zinc deficiency in wheat pot-grown on noncalcareous and calcareous soils of different properties

Abstract: The contents in carbonate-free clay-, silt-and sand-sized particle contents of the samples were determined with the pipette method after dispersion in sodium hexametaphosphate of decarbonated samples obtained by treating intact soil with a ~0.5 M HCl solution until production of CO 2 ceased. pH was determined by potentiometric measurement in a 1:2.5 w/v soil:water suspension; cation exchange capacity by extraction with 1 mol/L NH 4 OAc buffered at pH 7; exchangeable cations by atomic absorption (Ca and Mg) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…The twelve soils used in this study were obtained from the collection of 47 topsoil (0-25 cm) samples characterized by Sacristán et al (2019) [24] (see Table 1 and Table S1 in the Supplementary material). The selection of these soils was done based on several criteria: The soils were representative of the Mediterranean region, varied widely in their properties, covered a broad range of P content and were all Zn-poor soils, which resulted in an uneven P/Zn ratio.…”
Section: Soils and Soil Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The twelve soils used in this study were obtained from the collection of 47 topsoil (0-25 cm) samples characterized by Sacristán et al (2019) [24] (see Table 1 and Table S1 in the Supplementary material). The selection of these soils was done based on several criteria: The soils were representative of the Mediterranean region, varied widely in their properties, covered a broad range of P content and were all Zn-poor soils, which resulted in an uneven P/Zn ratio.…”
Section: Soils and Soil Propertiesmentioning
confidence: 99%
“…Significant (p < 0.05) differences are marked with an asterisk, Figure S3: Nature of soil × fungal treatment interaction in K and Na uptake by plants on soils pertaining to the GSGYI < 15 (those where grain yield was increased by less than 15%) inoculated with B. bassiana (A and B) or M. brunneum (C and D). Significant (p < 0.05) differences are marked with an asterisk, Figure S4: Nutrient availability of Control (white circles) against B. bassiana (black circles) treatment for Fe (A) and Cu (C) and against M. brunneum treatment (black squares) (B and D; respectively) in soils before (x-axis) and after (y-axis) cropping, Table S1: Additional soil properties ‡ of the soils described in Sacristán et al (2019) [24], Table S2: One-way ANOVA or Kruskal-Wallis test and comparison of means ‡ for wheat biomass, nutrient uptake and grain nutrient concentration (mean value, n = 18) on the different soils at harvest, Table S3: Factorial ANOVA (soil × fungal treatment) and Kruskall-Wallis test ( † , when data failed to fulfill the criteria for parametric analysis) for grain yield, straw and nutrient uptake of durum wheat plants grown on GSGYI < 15. § Significant differences (p < 0.05) are in boldface.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…negative impacts on water quality 1 . In addition, due to the relatively low nutrient uptake by crops in productive systems, 2 generous fertilization practices lead to soil nutrient imbalances and the consequent reduced absorption and antagonistic relationships between nutrients 3 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the Olsen test 21 for P and the diethylenetriaminepentaacetic acid‐extractable Zn (Zn DTPA ) test for Zn 22 have proven to be useful in studies dealing with the response of crops to the soil P and Zn levels 23–27 . Thus, Sacristán et al 3 . showed that the Olsen P and Zn DTPA levels as well as the Olsen P/Zn DTPA ratio were good predictors of the yield and nutrient content of durum wheat pot‐grown at different levels of P and Zn application.…”
Section: Introductionmentioning
confidence: 99%